Effects of timing and duration under brackish water mulch drip irrigation on cotton yield in northern Xinjiang, China - Chunxia, Wang; Guang, Yang; Junfeng, Li; Xinlin, He; Lianqing, Xue; Aihua, Long (International Journal of Agricultural and Biological Engineering, 2017)
The brackish water is an important potential water source and has frequently been utilized to drip-irrigate cotton due to the water shortage in the arid region of Xinjiang, northwestern of China. The brackish water is usually saline water with salinity ranging from 1 g/L to 5 g/L, which is widely distributed in this area, so the reasonable use of that brackish water may not only play a vital role in the local agricultural production, but also save plenty of freshwater. However, irrigation with brackish water usually causes the reduction of crop yield and soil salinization which can negatively impact plants through three major components: osmotic, nutritious and toxic stresses. Therefore, a field experiment, with eight different time-series irrigation modes using brackish water (3.5±0.2) g/L and freshwater, less than 1 g/L, beneath a combined film and drip-irrigation system was carried out to study the changes of soil salt content and cotton yield aiming to search for a balanced method during the 2 cotton growing seasons in 2012 and 2013. The results indicated that the time-series irrigation modes determined the soil salinity and moisture distribution based on observed spatio-temporal distribution of water content and electric conductivity, and soil salinity generally gathered at the depth of 0-10 cm and 60 cm of soil with the increase of irrigation quota. Moreover, the results demonstrated that the yields of cotton which was grown using brackish water and freshwater were better than those only using freshwater and the soil salinity with reasonable irrigation timing was not accumulated obviously. Keywords: brackish water, mulch drip irrigation, timing and duration for irrigation, irrigation scheduling, cotton DOI: 10.25165/j.ijabe.20171006.3108 Citation: Wang C X, Yang G, Li J F, He X L, Xue L Q, Long A H. Effects of timing and duration under brackish water mulch drip irrigation on cotton yield in northern Xinjiang, China. Int J Agric & Biol Eng, 2017; 10(6): 115–122.